Is self-care dialysis associated with social deprivation in a universal health care system? A cohort study with data from the Renal Epidemiology and Information Network Registry. Issue 5 (10th December 2019) - Beaumier, Mathilde; Béchade, Clémence; Dejardin, Olivier; Lassalle, Mathilde; Vigneau, Cécile; Longlune, Nathalie; Launay, Ludivine; Couchoud, Cécile; Ficheux, Maxence; Lobbedez, Thierry; Châtelet, Valérie
Abstract: Background: Socioeconomic status is associated with dialysis modality in developed countries. The main objective of this study was to investigate whether social deprivation, estimated by the European Deprivation Index (EDI), was associated with self-care dialysis in France. Methods: The EDI was calculated for patients who started dialysis in 2017. The event of interest was self-care dialysis 3 months after dialysis initiation [self-care peritoneal dialysis (PD) or satellite haemodialysis (HD)]. A logistic model was used for the statistical analysis, and a counterfactual approach was used for the causal mediation analysis. Results: Among the 9588 patients included, 2894 (30%) were in the most deprived quintile of the EDI. A total of 1402 patients were treated with self-care dialysis. In the multivariable analysis with the EDI in quintiles, there was no association between social deprivation and self-care dialysis. Compared with the other EDI quintiles, patients from Quintile 5 (most deprived quintile) were less likely to be on self-care dialysis (odds ratio 0.81, 95% confidence interval 0.71–0.93). Age, sex, emergency start, cardiovascular disease, chronic respiratory disease, cancer, severe disability, serum albumin and registration on the waiting list were associated with self-care dialysis. The EDI was not associated with self-care dialysis in either the HD or in the PD subgroups. Conclusions: In France, social deprivation estimated by the EDI is associated with self-care dialysis in end-stage renal disease patients undergoing replacement therapy.